Emotional Value Meets Digital Influence: Unveiling Factors Driving Slow Fashion Purchases in Indonesia - Hariningsih, Endang; Munarsih, Eni; Budiman, Santi (Jurnal Dinamika Manajemen, 2024)
This study explores the relationship between digital influences and consumer perceived emotional value in driving slow fashion purchases in Indonesia, an underexplored context in existing research. By examining the effects of online promotions, personalized recommendations, content marketing, social reviews, and perceived price-quality on consumer behavior, this research provides novel insights into effective marketing strategies for sustainable products. Empirical analysis validates the significant role of emotional value in shaping purchase intentions, with personalized recommendations and content marketing emerging as critical drivers. However, online promotions, social reviews, and perceived price-quality were found to have insignificant impacts on emotional value. These findings suggest that while online promotions and perceived price-quality are important, their impact on emotional value may be limited without integration with other strategies. This research uniquely contributes by highlighting specific digital and emotional factors that influence consumer behavior towards slow fashion products, supporting the development of more effective and targeted sustainable marketing strategies. This article could potentially be used for a broader exploration of the long-term impacts of these influences and provide a comprehensive understanding of consumer behavior in different contexts.